Determinants of Nordic entrepreneurship. Issue 1 (20th February 2017) - Dvouletý, Ondřej
Abstract : Purpose: The purpose of this paper is to analyse the determinants of entrepreneurial activity in the Nordic countries over the period of years 2004-2013 to provide supportive material for the Nordic entrepreneurial policy makers with specific focus on the role of necessity/opportunity-driven entrepreneurship, administrative barriers and the research and development (R&D) sector. Design/methodology/approach: Quantitative study employed panel regression analysis with fixed effects estimator to test the impact of determinants on entrepreneurial activity operationalized as a rate of registered business activity and as an established business ownership rate. Findings: The results obtained for the both dependent variables did not substantially differ from each other or the supported hypothesis stating a positive relationship between unemployment rate, GDP per capita and entrepreneurial activity. Also a negative impact of administrative barriers was found. However, no statistically significant positive impact of the R&D sector was observed. Practical implications: Nordic entrepreneurial policy makers should put more effort into the reduction of administrative barriers towards founding enterprises and support entrepreneurship during the times of higher unemployment rates. Further evaluation of Nordic R&D policies is strongly needed, since no positive impacts towards entrepreneurship were found. Originality/value: The empirical analysis was conducted based on the research gap in the studies related to the Nordic entrepreneurial policies and perceived need for the policy recommendations that are provided.